2022
DOI: 10.1101/2022.08.19.504465
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Inflation induced motility for long-distance vertical migration

Abstract: Living cells evolve under specific ecological conditions. The mass of our planet setting a constant gravitational pull and its daily rotation on its axis setting a circadian rhythm are two examples of universal ecological parameters that shape the physiology of every living creature on earth. In the ocean, gravity plays a critical role in shaping the life history of phytoplankton with vast diversity of size and cell geometries all depending on light to survive while gravity is pulling them down. In order to su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 84 publications
1
10
0
Order By: Relevance
“…can swim faster than the measured sinking velocities 40 , making upward migration from deeper ocean layers possible, given sufficient energy supply, which the accumulated carbohydrates can supply. Such ability of algae to vertically migrate long (~100 m) distances has been suggested before 2,41 , especially for non-motile species 2,15,16,42 . We therefore propose that the regulation of gravitational sinking in motile algae could impact marine carbon and nutrient fluxes, and this should be accounted for when modeling the marine nutrient and carbon fluxes 10,11 .…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…can swim faster than the measured sinking velocities 40 , making upward migration from deeper ocean layers possible, given sufficient energy supply, which the accumulated carbohydrates can supply. Such ability of algae to vertically migrate long (~100 m) distances has been suggested before 2,41 , especially for non-motile species 2,15,16,42 . We therefore propose that the regulation of gravitational sinking in motile algae could impact marine carbon and nutrient fluxes, and this should be accounted for when modeling the marine nutrient and carbon fluxes 10,11 .…”
Section: Discussionmentioning
confidence: 70%
“…In motile species, the ⅔-power law scaling of cell sinking may force larger cells to consume more energy to counteract excessive sinking. Because cell size increases in coordination with cell cycle progression [35][36][37] , the size-dependent sinking within a species can also result in cell cycledependent vertical positioning of the cells in the ocean, as seen in some non-motile species 15 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Structured metamaterials, like this chloroplast morphology, facilitate buckling and other complex deformations [45,46], enabling efficient chloroplast contraction under the confinement of the cell wall. Pyrocystis noctiluca, another species within the Pyrocystis genus, was found to have a reticulated cytoplasm, assisting with the vertical migration [50], showing another intricate link between the morphology of cytoplasmic space and its function in dinoflagellates. We also showed that the dynamics of chloroplast contraction can be effectively modeled using a "visco-elastic" framework with chemically controlled stress applications.…”
Section: Discussionmentioning
confidence: 99%
“…Pyrocystis spp . are known to live in the lower eutrophic zone at depths of 60 − 100 m [42] and undergo strong diurnal vertical migration [50]. The growth of P. lunula reaches full saturation under low light conditions found at approximately 50 m depth, equivalent to about 12 mW / cm 2 [67].…”
Section: Methodsmentioning
confidence: 99%